Characterization of the key aroma compounds in Semnostachya menglaensis Tsui by gas chromatography-olfactometry, odor activity values, aroma recombination, and omission analysis. (May 2020) - He, Chaojun; Li, Ziyong; Liu, Hongxia; Zhang, Haining; Wang, Liye; Chen, Hong
Graphical abstract: Highlights: Odor-active compounds of Semnostachya menglaensis Tsui were first detected. Twenty-nine odor-active compounds were perceived in five samples. Odor activity values, aroma recombination, and omission analysis were used. Four odor-active compounds were detected as the most potent compounds. Abstract: The aroma profile of Semnostachya menglaensis Tsui ( S. menglaensis ) was identified by headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography-olfactometry (GC-O) and gas chromatography–mass spectrometry (GC–MS). A total of 29 odor-active compounds, which have aroma intensities ranging from 0.2 ± 0.5 to 10.0 ± 0.0 were detected by GC-O, whereas 14 compounds were detected as important odorants by quantitative analysis and odor activity values (OAVs). An aroma recombination model prepared by mixing 12 odor-active compounds with OAVs ≥ 1 in an "aroma-free" S. menglaensis matrix showed good similarity to the aroma of original S. menglaensis. Omission tests showed that in the overall aroma of S. menglaensis, 2-propionyl-3, 4, 5, 6-tetrahydropyridine, 2-propionyl-1-pyrroline, 1-octen-3-ol, and linalool were the key odorants, and 2-acetyl-3, 4, 5, 6-tetrahydropyridine, 2-propionylpyridine, and α-ionone were also important.